Partisipasi Masyarakat dalam Pelaksanaan Program Sanitasi Total Berbasis Masyarakat di Kecamatan Palmerah Jakarta Barat - Titha Riharti Handayani; Rachmadi Purwana; Yeny Sulistyowati (Universitas Respati Indonesia, 2026)
Community-Based Total Sanitation (STBM) is a national strategy aimed at promoting hygienic and sanitation behavior change through community empowerment approaches. Despite various efforts to improve sanitation access, the implementation of STBM in densely populated urban areas still faces significant challenges, particularly related to the low level of community participation in program activities. This study aimed to analyze the relationship between community participation in the planning, implementation, and evaluation stages and the success of STBM implementation in Kemanggisan Village, Palmerah District, West Jakarta. This study employed a quantitative analytic design with a cross-sectional approach. The sample consisted of 210 respondents selected through simple random sampling from 425 targeted households. Data were collected using a structured questionnaire and analyzed through univariate analysis, bivariate analysis using the Chi-square test, and multivariate analysis using binary logistic regression. The results showed that community participation in the planning stage (p < 0.001; OR = 3.58), implementation stage (p < 0.001; OR = 1.71), and evaluation stage (p < 0.001; OR = 2.77) were significantly associated with the success of the STBM program. Multivariate analysis indicated that participation in the planning stage was the most dominant factor influencing program success (OR = 4.08), followed by participation in the evaluation stage (OR = 3.45). These findings highlight that active community involvement from the early planning stage to program evaluation plays a crucial role in improving the effectiveness and sustainability of community-based sanitation programs in urban areas. Strengthening community empowerment strategies by primary health centers and local governments through participatory planning and evaluation mechanisms is essential to accelerate the achievement of Open Defecation Free (ODF) status